Strategi Pemasaran Produk Pembiayaan Murabahah Lembaga Keuangan Syariah (Studi pada Baitul Mal Wat Tamwil Sunan Drajat Jawa Timur Cabang Tunggul Paciran Lamongan Jawa Timur) - Siswadi Siswadi; Iva Muslikhah N.A (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
Baitul Mal Wa Tamwil Financial Institution (BMT) has the task of collecting funds and distributing funds to the community. Baitul Mal Wa Tamwil in its management management must be able to arrange a good marketing strategy in achieving the goals of the institution, namely to attract consumers to use the products and services offered by BMT. The murabahah financing product is one of the products offered at BMT Sunan Drajat to people who need capital to open a small business or other businesses. This study aims to answer, describe, and analyze the focus of the problem, namely: (1) How is the marketing strategy in murabahah financing products at BMT Sunan Drajat. (2) What are the factors that hinder the implementation of the marketing of murabahah financing products. (3) What is the solution to overcome the obstacles in carrying out the marketing strategy of murabahah financing products. This research uses a qualitative approach, the data analysis method is carried out using deductive logic, to draw conclusions from general things to specific things that are specific or individual, research instruments use observation, interviews, documentation. The results of this study, it can be concluded that: The marketing strategy of murabahah financing products carried out by BMT Sunan Drajat Lamongan, namely by using a strategy to expand marketing by prioritizing affordable product prices, products needed by the community, promotions to attract customers, and an easy place recognized by prospective members (customers). Factors inhibiting marketing strategy Internal and External factors. The solutions carried out provide socialization to the public or prospective customers, promote products and provide understanding through social media, provide training to marketing personnel, select and sort out customers who apply for financing, increase the number of marketers to maximize product marketing.